The Effect of Social Constructivist SCAMPER Model on Creative Writing Skill - Alhamadi, Samaher AwaduAllah (International Journal of Linguistics, 2021)
This research was conducted with the aim of investigating the impact of social constructivist SCAMPER model on creative writing skill. Saudi students face difficulties in writing skill, especially in being required to memorize pieces of ready-written paragraphs without any understanding of what they should write and how. The participants were 30 female high school students studying in the third secondary school in Yanbu Industrial City. This study was a quantitative study. The participants were divided into an experimental and a control group. Data was collected by using a pre-post writing test and a questionnaire. The results showed that the social constructivist SCAMPER model had a positive effect on students’ creative writing skill. Also, based on the questionnaire, students showed a positive attitude toward using social constructivist SCAMPER model for developing creative writing. Based on the findings, the social constructivist SCAMPER model is highly recommended to be used in EFL writing classes in order to foster creative writing.